Estrategias metodológicas y su incidencia en el aprendizaje significativo de mantenimiento de motores a estudiantes de mecánica automotriz del Colegio Fiscal Simón Bolívar, ciudad Guayaquil - Chevez Herrera, Luis Alberto (2020)
The degree work called: “MTHODOLOGICAL STRATEGIES AND ITS INCIDENCE IN THE SIGNIFICANT LEARNING OF MOTORS MAINTENANCE TO STUDENTS OF AUTOMOTIVE MECHANICS OF THE FISCAL SCHOOL “SIMON BOLIVA”, CITY GUAYAQUIL”, HAS THE BEST STRATEGY TO PROMOTE: The learning system in our study. The objective pursued by this mechodogical proposal, a pedagogical situation is better is for teacher to use a variety of methodological stategies within the training system achieving significant learning is their students. As a result, it is determined that study teachers must use several methodological strategies in learning, to arouse interest in students and promote meaningful learning.